Mapping Dicorynia guianensis Amsh. wood constituents by submicron resolution cluster‐TOF‐SIMS imaging. (17th May 2016) - Vanbellingen, Quentin P.; Fu, Tingting; Bich, Claudia; Amusant, Nadine; Stien, Didier; Della‐Negra, Serge; Touboul, David; Brunelle, Alain
Abstract : The preparation of tropical wood surface sections for time‐of‐flight secondary ion mass spectrometry imaging is described, and the use of delayed extraction of secondary ions and its interest for the analysis of vegetal surface are shown. The method has been applied to the study by time‐of‐flight secondary ion mass spectrometry imaging with a resolution of less than one micron of a tropical wood species, Dicorynia guianensis, which is one of the most exploited wood in French Guiana for its durable heartwood. The heartwood of this species exhibits an economical importance, but its production is not controlled in forestry. Results show an increase of tryptamine from the transition zone and a concomitant decrease of inorganic ions and starch fragment ions. These experiments lead to a better understanding of the heartwood formation and the origin of the natural durability of D . guianensis . Copyright © 2016 John Wiley & Sons, Ltd.